Star Party Planner / Ana Nor Eryna Taip ... [ et al. ] - Taip, Ana Nor Eryna; Bodingin, Davina; Joseph, Easter; Albert, Prescilla Christy; Louis, Veronica Cyrila (2011)
The name of our company is Star Party Planner which is a partnership business that consists of five members. As agreed in our partnership agreement, each of the partners must contribute certain amount of capital. Our main activities are planning, designing and managing various kind of party such as birthday, baby showers, farewell party, welcoming party, warming party, bachelor and bachelor ate party and congratulation party. All of us have decided that the date of commencement for our business is on early 2013 located at The KK Times Square Office area. To ensure our business will run smoothly, each and every partner must give their full commitment and participation in managing this business. The General Manager for our company is Ana Nor Eryna Binti Taip, the Administrative Manager is Veronica Cyrila Louis, the Marketing Manager is Davina Bodingin, the Operation Manager is Easter Joseph and the Financial Manager is Prescilla Christy Albert. The General Manager is responsible to act as a leader in managing the team and the other manager will give their support by assisting the General Manager. The General Manager also is responsible in planning, organizing, leading, directing and coordinating the whole administration company. Other than managing the office environment, the Administration Manager is also responsible for gathering, adapting, storing and distributing any information about the company. Other than helping in promoting the sales and company, the Marketing Manager is also responsible in maintaining a positive attitude that promotes team work within the company and a favorable image of the company. The Operation Manager is responsible in controlling and monitoring the company operation department. This to ensure the productivity and quality of our company is at the excellent rate. Last but not least the Financial Manager who will handles any issues regarding the financial matters of the company. This includes preparing all the budgets and financial statement for any expenditure from all departments.